(untitled) (The Pakistan Development Review, 2007)
This paper examines whether the intensification of international competition widens the gap between developing and developed economies. The intensification of international competition with an influential trade union in the North is known to lower the North’s markup rate. This paper is unique because it points out that the intensification of international competition can widen the North-South gap when the Southern debt is taken into consideration. It also shows that the egalitarian policy in the North as influenced by trade unions is compatible with its international policy: relief of interest payments.